Space: A Final Frontier for Vacuolar Pathogens. (24th February 2016) - Case, Elizabeth Di Russo; Smith, Judith A.; Ficht, Thomas A.; Samuel, James E.; de Figueiredo, Paul
Abstract : Intracellular bacteria must appropriate host vesicular traffic and membrane fusion events to build pathogen‐specific niches. Here, we review the molecular mechanisms and trafficking pathways that drive two space allocation strategies of intracellular bacteria, the formation of tight and spacious pathogen‐containing vacuoles. We relate bacterial modulation of vacuolar space to its impact on critical facets of intracellular parasitism and discuss the evolutionary drivers that may have shaped their replicative vacuoles. Abstract : There is a fundamental gap in our understanding of how a eukaryotic cell apportions the limited space within its cell membrane. Upon infection, a cell competes with intracellular pathogens for control of this same precious resource. The struggle between pathogen and host provides us with an opportunity to uncover the mechanisms regulating subcellular space by understanding how pathogens modulate vesicular traffic and membrane fusion events to create a specialized compartment for replication. By comparing several important intracellular pathogens, we review the molecular mechanisms and trafficking pathways that drive two space allocation strategies, the formation of tight and spacious pathogen‐containing vacuoles. Additionally, we discuss the potential advantages of each pathogenic lifestyle, the broader implications these lifestyles might have for cellular biology and outline exciting opportunities for future investigation.